التأثيرات الإجتماعية والثقافية القرطاجية على النوميديين 814-146 ق-م - عيسى زعزاع; د. صبيحة أوكيل (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة : 146 ( من خلال دراسة الموضوع عن التأثيرات الاجتماعية والثقافية القرطاجية على النوميديين ق- م) حيث تطرقنا الى نبذة عن قرطاجة من خلال النشأة وعوامل التوسعات الفينيقية في الحوض الغربي 814 للبخر الأبيض المتوسط وصولا الى تأسيس مستوطنة قرطاجة وعلاقتها قبل وبعد القرن الخامس قبل الميلاد ثم الى مملكة نوميديا والحياة الاجتماعية في قرطاجة والعادات والتقاليد والحياة الدينية و الثقافية في قرطاجة والامتزاج الحضاري القرطاجي النوميدية حيث توصلنا الى التاثير المباشر وغير المباشر للقرطاجيين على النومديين. النوميديين– الكلمات المفتاحية: التأثيرات الاجتماعية والثقافية- القرطاجية Study summary: By studying the subject of the Carthaginian social and cultural influences on the Numidians (146-814 BC), we discussed an overview of Carthage through its development and the factors of Phoenician expansion in the western basin of the Mediterranean Sea, leading to the establishment of the Carthage settlement and its relationship before and after the fifth century BC, and then to The Kingdom of Numidia, social life in Carthage, customs and traditions, religious and cultural life in Carthage, and the Carthaginian-Numidian civilizational blend, where we reached the direct and indirect influence of the Carthaginians on the Numidians. Keywords: social and cultural influences - Carthaginian - Numidian